2003
DOI: 10.1097/01.mp.0000051990.80904.af
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Features of the Terminal Ileum in Lymphocytic and Collagenous Colitis: A Study of 32 Cases and Review of Literature

Abstract: Biopsy specimens from the terminal ileum of 32 patients with the histopathological diagnosis of lymphocytic colitis or collagenous colitis and 11 control individuals were evaluated for the presence or absence of ileal mucosal abnormalities and for the number of intraepithelial lymphocytes, assessed by immunohistochemical stains for the pan T-cell marker, CD3. We found that the mean CD3 counts in patients with lymphocytic/collagenous colitis were significantly higher than those in the control group. Seven of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…Elevated MCM7 expression has been reported in prostate (Padmanabhan et al, 2004), cervical (Brake et al, 2003), head and neck (Cromer et al, 2004) and pancreatic cancers (Grutzmann et al, 2004). In neuroblastoma, MCM7 is transcriptionally regulated by MYCN and increased expression was found to correlate with aggressive MYCN amplified tumors (Shohet et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Elevated MCM7 expression has been reported in prostate (Padmanabhan et al, 2004), cervical (Brake et al, 2003), head and neck (Cromer et al, 2004) and pancreatic cancers (Grutzmann et al, 2004). In neuroblastoma, MCM7 is transcriptionally regulated by MYCN and increased expression was found to correlate with aggressive MYCN amplified tumors (Shohet et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…However, so far only MCM7 has been reported to be highly expressed in the more aggressive (CIN III) as compared to the less aggressive (CIN II) high grade dysplasia in the cervix (Brake et al, 2003), whereas no differences in MCM2 or MCM5 could be found in CIN II and CIN III lesions. Additional studies have recently demonstrated that elevated MCM7 expression levels correlate with aggressive prostate cancer (Padmanabhan et al, 2004) and head and neck squamous cell carcinomas (HNSCC) (Cromer et al, 2004). Notably, MCM7 is the only MCM family member whose promoter contains an E-box sequence, which is the binding site for members of the MYC transcription factor family (Eisenman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, only 2 cases of CC associated with PLE have been reported [16,17]. PLE was not part of the clinical presentations in those adult patients who had gastric or small intestinal involvement with CC [6,7]. The exact mechanism of gastrointestinal protein loss in this condition is unknown, but abnormalities in the surface epithelium, superficial capillaries, and pericryptal fibroblast have been hypothesized [17].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, it is a disease of middle-aged women with a clinical picture characterized by nonbloody chronic watery diarrhea and histology showing a thickened subepithelial collagenous band [1]. There is growing evidence in adult literature that collagenous inflammatory mucosal disease is a more extensive Case Reports in Gastrointestinal Medicine pathologic process that concomitantly might involve several other gastrointestinal sites and not only the colon [6,7]. Searching the pediatric literature revealed more than twentyfour reported patients with collagenous gastritis [8], more than nine cases of collagenous colitis [3][4][5][9][10][11][12][13][14], one with gastrocolonic involvement [11], and one with involvement of gastric, duodenal, and colonic mucosa [15].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the previously reported intraepithelial lymphocytosis in terminal ileum in adult patients with CC. 26,27 While clinical trials have shown the efficacy of budesonide treatment in adult patients with CC, [28][29][30][31][32] treatment for children appears to be largely empiric with various agents (Table 1). Overall, sulfasalazine, mesalazine, and cholestyramine were either ineffective or only partially effective.…”
Section: Discussionmentioning
confidence: 99%